Methodical guidelines for performing laboratory assignments in the discipline "Algorithms and models for data collection, analysis, and visualization" and "Mathematical methods of data visualization" - Vodka, Oleksii O.; Shapovalova, Mariia I. (Національний технічний університет "Харківський політехнічний інститут", 2026)
The methodical guidelines present the basic concepts, methods, and practical approaches used in the study of the disciplines «Algorithms and Models for Data Collection, Analysis, and Visualization» and «Mathematical Methods of Data Visualization». The guidelines describe modern techniques of data visualization, mathematical models, and software tools for effective visual representation and analysis of data. The methodical guidelines correspond to the course programs «Algorithms and Models for Data Collection, Analysis, and Visualization» and «Mathematical Methods of Data Visualization» and contain the structure of laboratory assignments, theoretical background, and practical examples. Intended for students of higher educational institutions specializing in F1 «Applied Mathematics» and F3 «Computer Science».
Keywords: methodical guidelines; laboratory assignments; data collection; data visualization; mathematical methods; applied mathematics